PENDIDIKAN MODERASI BERAGAMA DALAM KELUARGA - Iqbal Anggia Yusuf (HASBUNA : Jurnal Pendidikan Islam, 2022)
The purpose of this study was to analyze the educational values ​​of religious moderation in the family that must be instilled in the family and analyze the supporting and inhibiting factors. This research uses this type of research. This study uses a type of qualitative research with library research (library research). The results of this study reveal that the first thing that must be instilled in children in the family is to get an education by inculcating religious values. The education process given to children can be done in several ways, namely through example, habituation, punishment, reward, and supervision. The process of religious moderation education in the family is carried out in two phases, the first is the pre-natal education phase which consists of the pre-conception period and the post-conception period. The second is the post-natal education phase which consists of infancy, childhood, childhood, adolescence, and adulthood.